Analysis of Mn-deposits from the Pacific - Piper, David Z (Supplement to: Piper, DZ (1974): Rare earth elements in ferromanganese nodules and other marine phases. Geochimica et Cosmochimica Acta, 38(7), 1007-1022, https://doi.org/10.1016/0016-7037(74)90002-7, 1974)
The concentrations of rare-earth elements (REE) have been measured in 31 ferromanganese nodules from the Pacific and Indian Oceans and vary by almost a factor of 5. Too few nodules have been analyzed to define possible regional trends. The shale-normalized patterns, however, permit division of nodules into two groups: those from depth greater than 3000–3500 m and those from less depth. The factors that determine this change in the relative concentration of REE may be related to the mineralogy of manganese phases and/or the transport of REE to the deep ocean by particulate matter. Comparison of the REE patterns of nodules with those of phillipsite, phosphorite, clays, CaCO3 and seawater suggests that the patterns of these phases reflect fractionation from an initial pattern closely resembling that of shale. By assuming that the accumulation rate of REE in clays, CaCO3 and nodules is represented by that for surface sediments, it has been possible to estimate an accumulation rate of phillipsite in pelagic sediments of the Pacific of 0.02 mg/cm2/yr.